Guest Editorial: ICTs for Developing Countries – Are There Realistic Answers to the Difficult Problems? - Wenn , Andrew (Journal of Law and Governance, 2007)
Welcome, to this, the first special edition of the Journal for Business Systems, Governance and Ethics. This issue is devoted entirely to the problems of deploying, using and maintaining information and communications technology (ICT) in lesser-developed countries (LDCs). When the call for submissions for this special issue went out in late 2006, this journal was less than 12 months old, although, of course, it had been in the planning stages for longer than this.